Altered neutrophil-to-lymphocyte ratio in sepsis secondary to canine parvoviral enteritis treated with and without an immunomodulator in puppies - Muñoz, Adriana I.; Maldonado-García, José Luis; Fragozo, Ana; Vallejo-Castillo, Luis; Lucas-Gonzalez, Amellalli; Trejo-Martínez, Ismael; Pavón, Lenin; Pérez-Sánchez, Gilberto; Cobos-Marin, Laura; Pérez-Tapia, Sonia Mayra (Frontiers in Veterinary Science, 2022)
Neutrophil-to-lymphocyte ratio (NLR) is a cheap and easy-to-obtain biomarker that mirrors the balance between innate and adaptive immunity. Cortisol and catecholamines have been identified as major drivers of NLR. High cortisol levels increase neutrophils while simultaneously decreasing lymphocyte counts. Likewise, endogenous catecholamines may cause leukocytosis and lymphopenia. Thus, NLR allows us to monitor patient severity in conditions such as sepsis. Twenty-six puppies with sepsis secondary to canine parvoviral enteritis were treated with and without an immunomodulator. Our group determined the NLR and the plasmatic cortisol levels by chemiluminescence, and norepinephrine (NE) and epinephrine (E) by HPLC during the first 72 h of clinical follow-up. Our results showed that at admission puppies presented an NLR value of 1.8, cortisol of 314.9 nmol/L, NE 3.7, and E 3.3 pmol/mL. Both treatments decreased admission NLR values after 24 h of treatment. However, only the puppies treated with the immunomodulator (I) remained without significant changes in NLR (0.7–1.4) compared to the CT group, and that showed a significant difference (P < 0.01) in their NLR value (0.4–4.6). In addition, we found significant differences in the slope values between the admission and final values of NLR (P < 0.005), cortisol (P < 0.02), and E (P < 0.05) between treatments. Then, our data suggest that the immunomodulator positively affects the number of lymphocytes and neutrophils involved in NLR as well as major drivers like cortisol and epinephrine, which is reflected in clinical parameters and survival.